Climate change mitigation policy and human health: Evidence from the forest farm carbon sink projects in China - Jian Liu; Yanjun Ren; Thomas Glauben; Zhanli Sun (Environmental Impact Assessment Review, 2026)
Forest Farm Carbon Sink Projects (FFCSPs) represent a promising strategy for mitigating global climate change and improving public health. While the direct effects of such projects on carbon sequestration and participants' income are well researched, the potential co-benefits of FFCSPs on human health remain underexplored. The study bridges this research gap by examining the causal effect of FFCSPs on human health, measured through healthcare costs and the number of physician visits. Based on a panel dataset covering 140 counties in Sichuan, China, from 2002 to 2018, we employ Propensity Score Matching and Difference-in-Differences (PSM-DID) to mitigate potential endogeneity concerns. Our findings show that FFCSPs can significantly reduce healthcare costs by approximately 12.8% and decrease the number of physician visits by 0.31 times per resident per year. These health benefits primarily result from improvements in socioeconomic and ecological conditions, such as industrial upgrading, economic gains through income growth, and better air quality. Notably, these benefits are observed only in international projects and are absent in domestic initiatives. This study highlights the dual benefits of FFCSPs, showing that policies promoting these projects can simultaneously improve public health and achieve environmental goals. To fully realize these benefits, effective implementation methods, clear enforcement standards, effective regulation, and well-functioning carbon trading platforms are essential.
Keywords: 630; climate change; forest carbon sink; public health; carbon emissions; difference-in-differences; China